Stretchable Supercapacitors: From Materials and Structures to Devices. Issue 1 (13th December 2020) - Shao, Guangwei; Yu, Rui; Chen, Nanliang; Ye, Meidan; Liu, Xiang Yang
Abstract: Stretchable supercapacitors have received widespread attention due to their potential applications in wearable electronics and health monitoring. Stretchable supercapacitors not only possess advantages such as high power density, long cycle life, safety, and low cost of conventional supercapacitors but also have excellent flexibility and stretchability, which make them well integrated with other wearable systems. In this review, various strategies to fabricate stretchable supercapacitors are focused. The preparation methods for stretchable electrodes/devices in the literature are carefully classified and analyzed. Three strategies for preparing stretchable electrodes/devices are summarized in detail—the design of elastic polymer substrates, stretchable electrode structures, and composite electrodes combined with elastic polymers and stretchable structures. Meanwhile, the interface problem of electrodes/devices in the stretching process is studied in depth. The research progress of multifunctional stretchable supercapacitors is also introduced. Finally, challenges and possible solutions that still need to be addressed in the future development of stretchable supercapacitors are highlighted and prospected. This review comprehensively discusses the latest research progress in the field of stretchable supercapacitors and systematically elucidates the electrochemical and mechanical properties of these devices, hoping to improve the roadmap for scientists and engineers to develop supercapacitors with high electrochemical performance and good stretchability. Abstract : Three strategies for preparing stretchable supercapacitors are summarized emphatically—selection of elastic polymers, design of stretchable structures, and design of composite electrodes of elastic polymers and stretchable structures. This review summarizes the generally applicable experience, hoping to improve the roadmap for scientists and engineers to develop supercapacitors with high electrochemical performance and good stretchability.